Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2022
DOI: 10.3389/fphar.2022.1026337
|View full text |Cite
|
Sign up to set email alerts
|

TKI or TKI combined with PD-1 inhibitors as second-line treatment for HCC patients after sorafenib failure

Abstract: Background: Tyrosine kinase inhibitors (TKI) in combination with programmed cell death-1 (PD-1) inhibitors become the potential treatment modality for patients undergoing unresectable hepatocellular carcinoma (uHCC) in the first-line setting. However, the efficacy and safety of this combination regimen in patients after sorafenib failure remains unclear.Methods: Participants in this study included patients with uHCC after sorafenib failure who received TKI monotherapy (TKI group) or TKI combined with PD-1 inhi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 39 publications
0
2
0
Order By: Relevance
“…In a phase II trial RESCUE, the DCR was > 77% in the first-line and 75% in the second-line advanced HCC cohort treated with camrelizumab combined with apatinib 15 . Additionally, a recent study demonstrated that a combination of TKI-PD-1 was found to be more advantageous than TKI monotherapy for HCC patients who had previously failed sorafenib treatment 10 . This suggests that TKI-PD-1 therapy could be a promising treatment option for advanced HCC after first-line therapy failure.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In a phase II trial RESCUE, the DCR was > 77% in the first-line and 75% in the second-line advanced HCC cohort treated with camrelizumab combined with apatinib 15 . Additionally, a recent study demonstrated that a combination of TKI-PD-1 was found to be more advantageous than TKI monotherapy for HCC patients who had previously failed sorafenib treatment 10 . This suggests that TKI-PD-1 therapy could be a promising treatment option for advanced HCC after first-line therapy failure.…”
Section: Discussionmentioning
confidence: 99%
“…The Barcelona Clinic Liver Cancer (BCLC) guidelines still regard treatment after first-line failure as an area of ongoing research 9 . Between July 2018 and July 2021, Lei et al conducted a study involving patients with unresectable HCC (uHCC) who had failed sorafenib treatment 10 . They discovered that a combination of TKI and PD-1 inhibitors (TKI-PD-1) was more advantageous than TKI monotherapy for these patients, indicating that TKI-PD-1 therapy could be a promising treatment option for advanced HCC after first-line failure.…”
Section: Introductionmentioning
confidence: 99%